Revisiting representative form in ISIS media: How emerging collectives reconstitute communities in the 21st century - Winkler, Carol K. (Frontiers in Communication, 2022)
This essay reconsiders the concepts of representative form and visual ideographs in the context of collectives-in-formation that are heavily reliant on the online environment to communicate with global audiences. Focusing on the online media products of ISIS, the study conducts a quantitative content analysis of over 9000 images that the group distributed from 2014-2020, coupled with a qualitative assessment of the group’s religious and institutional contexts. The findings add to current understandings of how reconstituted communities develop visual ideographs by showing how predictable constellations of iconic and non-iconic compositional elements combine to create representative characters and how non-parodied images can also function ideographically. The study also demonstrates how institutional definitions can serve as critical intervening variables for understanding the reinforcing relationship between icons and verbal ideographs.